Ready, set, go!: Why are some regions entrepreneurial jump-starters? - Michael Wyrwich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Previous research on market economies characterized by stable framework conditions shows that several regional factors determine start-up activity. Not much is known about what drives entrepreneurship in unstable environments characterized by significant institutional changes that affect the availability of entrepreneurial opportunities. To fill this gap, this paper focuses on post- communist regions in which start-up activity was basically nonexistent under socialism but significantly more in evidence after the institutional shock of introducing a market economy. It is argued and shown that the allocation of talent into productive entrepreneurship is higher in areas abundantly endowed with individuals who have a relatively high ability to detect viable entrepreneurial opportunities, as indicated by their qualification, and in regions home to a population that is characterized by a high alertness toward opportunities, as indicated by remnants of an entrepreneurial culture that pre- dates socialism. How institutional context affects entrepreneurship over the course of transition is reflected by the negative relationship between urbanization and entrepreneurship that presumably has to do with ill-devised socialist urban planning policies. The regional application of the theory on institutions and entrepreneurship outlined in this paper shows that an entrepreneurial rebound after an adverse large-scale shock accompanied by massive structural change and economic dislocation is most pronounced in areas with a strong human capital basis and a regional culture that favors entrepreneurship.
Keywords: L26; R1; P25; 330; entrepreneurship; regional knowledge; transition